Focus of the right to mental health according to the constitutional court in compliance with the new Mental Health Law: an analysis from a sentence of the Peruvian Constitutional Court in concordance with the new Mental Health Law - Franciskovic Ingunza, Beatríz (2019)
The present jurisprudential comment describes a judgment of the Peruvian Constitutional Court regarding a case in which the violation of the Law of Mental Health is alleged. It will be analyzed what is meant by the Right to Health, mental health, the regulation in this respect that exists in Peru until the new Law of Mental Health, as well as the function or work of the State in front of this fundamental right